1984
DOI: 10.1177/019459988409200511
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progesterone Receptors in Hereditary Hemorrhagic Telangiectasia

Abstract: Hereditary hemorrhagic telangiectasia (HHT) often requires transfusion and has major ill-effects. The recent literature reports successful highdose estrogen treatment of epistaxis caused by HHT. To investigate this, biopsy specimens taken from areas clinically involved with telangiectasia in four patients were evaluated for estrogen-and progesteronebinding receptors. Specimens from two women (ages 34 and 38) were positive for both estrogen and progesterone receptors in ranges observed in breast carcinoma speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 16 publications
0
26
0
2
Order By: Relevance
“…This may reflect a fundamental modification of the HHT vasculature by female hormones, or relate to haemodynamic changes during pregnancy 63. A role for direct hormonal influences is supported by the successful treatment of HHT related gastrointestinal bleeding using combined oestrogen-progesterone therapy,21 a report of progesterone receptors in vessels of patients with HHT,144 and variations in epistaxis during the menstrual cycle and menopause 63. Haemodynamic changes can also exacerbate PAVMs, including the development of pulmonary hypertension as a result of mitral stenosis145or left ventricular dysfunction 146.…”
Section: Current Understandings Of Mechanismsmentioning
confidence: 99%
“…This may reflect a fundamental modification of the HHT vasculature by female hormones, or relate to haemodynamic changes during pregnancy 63. A role for direct hormonal influences is supported by the successful treatment of HHT related gastrointestinal bleeding using combined oestrogen-progesterone therapy,21 a report of progesterone receptors in vessels of patients with HHT,144 and variations in epistaxis during the menstrual cycle and menopause 63. Haemodynamic changes can also exacerbate PAVMs, including the development of pulmonary hypertension as a result of mitral stenosis145or left ventricular dysfunction 146.…”
Section: Current Understandings Of Mechanismsmentioning
confidence: 99%
“…Estrogens increase plasma vWF levels in both normal as well as vWd patients and birth control pills have been used to control menorrhagia in patients with vWd. Finally, estrogen and progesterone receptors have also been demonstrated in the nasal tissue and skin of four patients with AVMs but not in the tissue of normal controls [34].…”
Section: Discussionmentioning
confidence: 94%
“…Reviewing the related literature, only two articles were found that addressed the detection of estrogen and progesterone receptors in tissue specimens of HHT patients [17,18]. Richtsmeier et al [17] examined a small sample of three biopsies using a ligandbinding assay and found progesterone receptors in three of three nasal mucosa specimens, two of which also contained estrogen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Richtsmeier et al [17] examined a small sample of three biopsies using a ligandbinding assay and found progesterone receptors in three of three nasal mucosa specimens, two of which also contained estrogen receptors. In 2000, Pau et al presented their study after using the more sensitive immunohistochemistry [18].…”
Section: Discussionmentioning
confidence: 99%